In-plane crushing behavior and energy absorption of a novel graded honeycomb from hierarchical architecture - Liu, Hu (2022)
Nature’s bio-organisms are typically hybrid structures composed of hierarchical and functionally graded micro-architectures, which are lightweight and of high mechanical performances. Inspired by nature, an innovative graded hierarchical honeycomb is proposed in this study to enhance its crashworthiness behaviors. The structure is created by replacing cell walls of regular honeycombs with triangular and hexagonal sub-structures and varying the hierarchical length ratio in each layer. The in-plane crushing performances of the graded hierarchical honeycombs are comprehensively analyzed and compared with their uniform hierarchical counterpart. The former exhibits a progressive deformation model under different impact velocities and three plateau stages can be observed under in-plane crushing loads through theoretical predictions. The triangular sub-structure presents better energy absorption than the hexagonal sub-structure, and its specific energy absorption is enhanced by up to 32.2% as compared to the uniform hierarchical honeycomb. The present study suggests that the combination of hierarchy and gradient is an effective strategy to improve the dynamic crushing behaviors of honeycombs, which can be further explored in protective devices to enhance their impact resistance.